Combined particle-image velocimetry and force analysis of the three-dimensional fluid–structure interaction of a natural owl wing. (1st April 2016) - Winzen, A; Roidl, B; Schröder, W
Abstract: Low-speed aerodynamics has gained increasing interest due to its relevance for the design process of small flying air vehicles. These small aircraft operate at similar aerodynamic conditions as, e.g. birds which therefore can serve as role models of how to overcome the well-known problems of low Reynolds number flight. The flight of the barn owl is characterized by a very low flight velocity in conjunction with a low noise emission and a high level of maneuverability at stable flight conditions. To investigate the complex three-dimensional flow field and the corresponding local structural deformation in combination with their influence on the resulting aerodynamic forces, time-resolved stereoscopic particle-image velocimetry and force and moment measurements are performed on a prepared natural barn owl wing. Several spanwise positions are measured via PIV in a range of angles of attack 6° and Reynolds numbers 40 000 120 000 based on the chord length. Additionally, the resulting forces and moments are recorded for −10° ≤  α  ≤ 15° at the same Reynolds numbers. Depending on the spanwise position, the angle of attack, and the Reynolds number, the flow field on the wing's pressure side is characterized by either a region of flow separation, causing large-scale vortical structures which lead to a time-dependent deflection of the flexible wing structure or wing regions showing no instantaneous deflection but a reduction of the time-averaged mean wing curvature. Based on the force measurements the three-dimensional fluid–structure interaction is assumed to considerably impact the aerodynamic forces acting on the wing leading to a strong mechanical loading of the interface between the wing and body. These time-depending loads which result from the flexibility of the wing should be taken into consideration for the design of future small flying air vehicles using flexible wing structures.